Lagos: Ownership and Identities Exhibition Essay - Lawanson, Taibat; Eleshin, Abisoye (Lagos Ownership and Identities (Intellectual Debates and One Month Photography Exhibition), 2021)
Video recording of opening panel session
Keywords: History; Migration; African Studies; Lagos; Knowledge